1975
DOI: 10.1017/s0022172400047227
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosainfection in hospital: a comparison between ‘infective’ and ‘environmental’ strains

Abstract: One hundred and fifty-six infections or episodes of infection associated with Pseudomonas aeruginosa in six hospitals over 14 months were investigated. Pyocine typing and serotyping suggested that 145 distinct episodes had occurred, caused by 78 different strains. During this period 15 distinct strains were isolated from the environment at one of the hospitals; 12 of these were apparently unassociated with infection in the same ward during the period, and 4 were of types not encountered in infective processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Liu (1966) showed that the organism has the ability to produce lecithinase, lipase and protease, 3 enzymes needed for tissue invasion. Al-Dujaili and Harris (1975) showed that the production of haemolysin by infective strains differentiated them from environmental strains. Liu (1964) showed that the pathological effect of the organism was caused by extracellular toxins and that the production of these toxins was enhanced when colonising damaged tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Liu (1966) showed that the organism has the ability to produce lecithinase, lipase and protease, 3 enzymes needed for tissue invasion. Al-Dujaili and Harris (1975) showed that the production of haemolysin by infective strains differentiated them from environmental strains. Liu (1964) showed that the pathological effect of the organism was caused by extracellular toxins and that the production of these toxins was enhanced when colonising damaged tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one cannot exclude the possibility of hospital infection caused by strains of B. fragilis prevalent in the various hospitals. Patients could acquire new hospital strains, similar to Escherichia coli (Cooke, Ewins & Shooter, 1969) and to Pseudomonas aeruginosa (Al-Dujaili & Harris, 1975 …”
Section: Discussionmentioning
confidence: 99%
“…However, not all colonised patients become infected with these organisms even when they are present in the patient's immediate environment. Al-Dujaili and Harris (1975) have looked at the colony morphology, pyocine typing, and haemolysin production of Ps. aeruginosa in the sputum from hospitalised patients and from their environment to try to discover when Ps.…”
Section: Discussionmentioning
confidence: 99%